Highly rigid and functional poly(benzimidazole sulfone)s from 5, 6‐dimethoxy‐1, 3‐dihydro‐2H‐benzo[d]imidazol‐2‐one monomer. Issue 5 (25th January 2023) - Xu, Wei; Su, Yumiao; Ding, Yulin; Li, Chenjie; Li, Wenmu
Abstract: A series of poly(benzimidazole sulfone)s (PBSs) and poly(benzimidazole ketone)s (PBKs) containing 5, 6‐dimethoxy‐1, 3‐dihydro‐2 H ‐benzo[ d ]imidazol‐2‐one (MBIO) have been synthesized by C–N/C–O coupling with different percentages of three other diphenol monomers under similar conditions. The structure of PBS‐MBs and PBK‐MBs was confirmed using 1 H NMR and Fourier transform infrared spectroscopies, and X‐ray diffraction data revealed that all the polymers are in an amorphous state. Due to the introduction of methoxy, the polymers were more soluble in common aprotic polar solvents. The intrinsic viscosity of the synthesized polymers was measured with an Ubbelohde viscometer, ranging from 0.38 to 1.35 dL g −1 . The MBIO‐based polymers have a remarkably good thermal stability with a high glass transition temperature of up to 305.1 °C. Furthermore, the wavelength of maximum fluorescence emission from homopolymers is around 414 nm with emission of blue light in N ‐methyl‐2‐pyrrolidone solution (1 mg L −1 ) and around 530 nm in films. They also showed low dielectric constants ( κ  = 2.60–3.10 at 1 MHz) and low water absorption (0.22–0.58%). It was encouraging to discover that these polymers have potential utility for the microelectronics industry, in which good solubility facilitates processing and molding, excellent thermal stability allows devices to be used under harsh conditions, low water absorption prevents device expansion and shrinkage and low dielectric constant is desired to prevent crosstalk between conducting paths. © 2023 Society of Industrial Chemistry. Abstract : Good thermal performance. Good solubility. Subsequent reaction site. Fluorescence properties. Low dielectric constant. A series of high‐performance poly (benzimidazole sulfone)s (PBSs) and poly (benzimidazole ketone)s (PBKs) containing 5, 6‐dimethoxy‐1, 3‐dihydro‐2H‐benzo[d]imidazol‐2‐one(MBIO) were synthesized by C‐N/C‐O coupling reaction.